2021
DOI: 10.21203/rs.3.rs-805463/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Optimizing self-pollinated crop breeding employing genomic selection: from schemes to updating training sets

Abstract: Long-term breeding schemes employing genomic selection (GS) can boost the response to selection per year. Although several studies show that GS delivers a higher response to selection, only a few analyze the best strategy to employ it, specifically how often and in what manner the training set (TS) should be updated. Therefore, we used stochastic simulation to compare in a long-term breeding program of a hypothetical self-pollinated crop five different strategies to implement GS in the line fixation stage and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 50 publications
(70 reference statements)
0
4
0
Order By: Relevance
“…Several studies have reported an increase in response to selection in breeding schemes using GS (Gorjanc et al 2018;Muleta et al 2019;DoVale et al 2021;Sabadin et al 2021). However, to increase the GS-based breeding program e ciency, it is essential to decide how and at which stage to apply this tool (Sabadin et al 2021). Usually, this increase is due to the shortening of the breeding cycle, which can be logistically challenging.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Several studies have reported an increase in response to selection in breeding schemes using GS (Gorjanc et al 2018;Muleta et al 2019;DoVale et al 2021;Sabadin et al 2021). However, to increase the GS-based breeding program e ciency, it is essential to decide how and at which stage to apply this tool (Sabadin et al 2021). Usually, this increase is due to the shortening of the breeding cycle, which can be logistically challenging.…”
Section: Discussionmentioning
confidence: 99%
“…In this context, our results showed that even using a low-density marker set, it is possible to keep the accuracy at levels that provide genetic gain over many breeding cycles however there is a need to update the TS properly. Furthermore, as described by (Sabadin et al 2021), the GPO updating method promotes more accurate estimates of LD between markers and QTL since, in long-term breeding schemes, recombination between marker and QTL causes an LD decrease. In contrast, selection and drift generate new LD or tighten the LD between closely linked loci.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations